New insights into centromeres from Arabidopsis Col-CEN assembly. Issue 5 (May 2022) - Yan, An; Yu, Hao
Abstract : Centromeres have an essential and conserved role in eukaryotes, and represent a paradoxical feature of rapid evolution. A recent study by Naish et al. applied long-read sequencing to survey a genome assembly of all five Arabidopsis ( Arabidopsis thaliana ) centromeres. Analyses of these centromeres showed characteristic genetic and epigenetic features, providing new insights into centromere evolution.